Vinegar residue supported nanoscale zero-valent iron: Remediation of hexavalent chromium in soil. (January 2020) - Pei, Guangpeng; Zhu, Yuen; Wen, Junguo; Pei, Yanxi; Li, Hua
Abstract: A composite material comprising of nanoscale zero-valent iron (nZVI) supported on vinegar residue (nZVI@VR) was prepared and applied for remediation of soils contaminated by hexavalent chromium (Cr(VI)). Sedimentation test results revealed that the nZVI@VR displayed enhanced stability in comparison to the bare-nZVI. Remediation experiments exhibited the immobilization efficiency of Cr(VI) and Crtotal was 98.68% and 92.09%, respectively, when using 10 g nZVI@VR (nZVI 5%) per 200 g Cr-contaminated soil (198.20 mg kg −1 Cr(VI), 387.24 mg kg −1 Crtotal ) after two weeks of incubation. Further analyses demonstrated that almost all the exchangeable Cr was transformed into Fe–Mn oxide bound and organic matter bound. Moreover, the application of nZVI@VR enhanced soil organic carbon content and reduced redox potential. After granulation, the immobilization efficiency of Cr(VI) and Crtotal achieved 100% and 91.83% at a dosage of 10% granular nZVI@VR. Granular nZVI@VR also accelerated the transform of more available Cr (exchangeable and bound to carbonates) into less available fractions (Fe–Mn oxide bound and organic matter bound), thus resulting in a remarkable reduction in the Cr bioavailability. These results prove that nZVI@VR can be an effective remediation reagent for soils contaminated by Cr(VI). Graphical abstract: Image 1 Highlights: nZVI@VR was synthesized and employed for remediation of Cr(VI)-contaminated soil. nZVI@VR or granular nZVI@VR have high immobilization efficiency of Cr(VI) and Crtotal in soil. nZVI@VR or granular nZVI@VR could promoted the conversion of more accessible Cr into the less accessible forms.